Reciprocal regulation of TNF receptor 1–mediated signaling and inflammatory damages by MARCH2 and USP22 - Hui-Fang Li; Rui Liu; Peng Ren; Hong-Bing Shu; Shu Li (Proceedings of the National Academy of Sciences, 2026)
The tumor necrosis factor (TNF) receptor 1 (TNF-R1) plays critical roles in inflammatory response and autoimmune diseases. The underlying mechanisms on posttranslational regulation of TNF-R1 and its functional significance remain enigmatic. In this study, we identified the deubiquitinase USP22 as a positive regulator of TNF-R1. USP22 is minimally associated with TNF-R1, which is markedly increased following TNF stimulation. USP22 deconjugates K27-linked polyubiquitination of TNF-R1 at K340, which reverses its proteasomal degradation. USP22 deficiency reduces TNF-triggered signaling and transcriptional induction of proinflammatory genes in human cell lines and primary mouse immune cells. Conversely, the membrane-associated E3 ligase MARCH2 is constitutively associated with TNF-R1, resulting in K27-linked polyubiquitination of TNF-R1 at K340 and its proteasomal degradation. MARCH2 deficiency promotes TNF-triggered signaling in various cell types. In mice, USP22 deficiency alleviates imiquimod (IMQ)-induced psoriasis-like dermatitis with reduced inflammatory cell infiltration and splenomegaly. In an acute liver injury model, USP22 deficiency reduces TNF/D-gal-induced inflammatory cytokine expression, liver damage, and inflammatory death, whereas MARCH2 deficiency increases TNF/D-gal-induced inflammatory cytokine expression and exacerbates pathological features of acute liver injury. These findings demonstrate that MARCH2 and USP22 reciprocally regulate K27-linked polyubiquitination and stability of TNF-R1, revealing regulatory mechanisms on TNF-R1-mediated inflammatory response.